The impact of the COVID-19 pandemic on the provision of HIV/AIDS-related services in Iran: a qualitative study - Zahra Jaafari; Hossein Mirzaei; Yousef Moradi; Naser Nasiri; Soheil Mehmandoost; Mehrdad Khezri; Fatemeh Tavakoli; Samaneh Abbaszadeh; Hamid Sharifi (BMC Health Services Research, 2023)
Abstract Background Providing services to people living with HIV (PLWH) faced many challenges during the COVID-19 pandemic. This study aimed to examine the impact of the COVID-19 pandemic on providing HIV/AIDS-related services in Iran. Methods In this qualitative study, the participants were included by purposive sampling between November 2021 and February 2022. Virtually focused group discussion (FGD) meetings were conducted with the first group including policymakers, service providers, and researchers (n = 17), and the interviews were conducted telephonic and face-to-face using a semi-structured guide with the second group including people who received services (n = 38). Data were analyzed by content analysis using the inductive method in MAXQDA 10 software. Results Six categories were obtained, including mostly affected services, ways of the effect of COVID-19, healthcare systems reaction, effects on social inequality, opportunities created by the pandemic, and suggestions for the future. In addition, people who received services believed the COVID-19 pandemic has affected their life in several ways, including getting COVID-19, mental and emotional problems during the pandemic, financial problems, changes in the care plan, and changes in high-risk behaviors. Conclusion Considering the level of community involvement with the issue of COVID-19 and the shock caused by the pandemic, as mentioned by the world health organization, it is necessary to improve health systems’ resilience for better preparedness for similar conditions.